An economic model assessing the value of microneedle patch delivery of the seasonal influenza vaccine. Issue 37 (8th September 2015) - Lee, Bruce Y.; Bartsch, Sarah M.; Mvundura, Mercy; Jarrahian, Courtney; Zapf, Kristina M.; Marinan, Kathleen; Wateska, Angela R.; Snyder, Bill; Swaminathan, Savitha; Jacoby, Erica; Norman, James J.; Prausnitz, Mark R.; et al.
Highlights Microneedle patches (MNPs) may bring potential advantages over existing vaccine technologies. We evaluated their potential economic and epidemiologic impacts in various vaccination settings. Administered by healthcare providers, MNPs would be cost-effective under most conditions tested. Self-administration may have a reduced administration success and fewer effective vaccinations. Efficacy or compliance increases could offset reduced self-administration success.